Antara Leviathan Dan Hukum Ikan - AAGN Ari Dwipayana (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 1999)
The origin of state has been the most intricate debate in political sciences since there is a scarcihy of strong physical evidence of what and how state initially horn and formated. It then explains why the discourse of state origin theory in political sciences featured is abstract-speculatif character, rather than empirical-based theory. The Contract Social theory is one of the most widely-known of the origin of state theory. In fact the theory of social contract is not merely western-based theory, yet it is also found the eastern political sphere, in Hindu tradition. This paper will examine thoroughly the social contract theory existing both in western and eastern academic tradistion. It compares Hobbes thought on Leviathan, and Kautilya, a scholar from the Hinduism tradition, who used to be a Prime Minister of Candragupta of Maurya Dinasty around 321-300 BC. This paper found that there is a similarihy between these two scholars on the certain stage of state origin namely the State of nature, a stage before the existence of state. Hobbes describes this stage as homo hoinoni lupus. The holy book Artasastra, written by Knit tilya has a similar content. Kau tilya used fish life as a metaphor, and calls his theory as the fish law, to describe the state of nature as